The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00402-012-1499-2
|View full text |Cite
|
Sign up to set email alerts
|

7-year follow-up after open reduction and internal screw fixation in Bennett fractures

Abstract: Background Bennett fractures are unstable, and, with inadequate treatment, lead to osteoarthritis, weakness and loss of function of the first carpometacarpal joint. This study focuses on long-term functional and radiological outcomes after open reduction and internal fixation. Methods Between June 1997 and December 2005, 24 patients with Bennett fractures were treated with open reduction and internal fixation with screws at our center. Radiological and functional assessments including range of motion of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 21 publications
(25 reference statements)
0
17
1
3
Order By: Relevance
“…19 The aim of treatment of these articular fractures is to obtain anatomic reduction. 7 Lutz and colleagues reported results at mean follow-up of 7 years comparing open screw fixation and percutaneous transarticular K-wire fixation of 32 large-fragment Bennett fractures. 20 Leclère and colleagues reported the long-term results of open screw fixation of 21 large-fragment Bennett fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The aim of treatment of these articular fractures is to obtain anatomic reduction. 7 Lutz and colleagues reported results at mean follow-up of 7 years comparing open screw fixation and percutaneous transarticular K-wire fixation of 32 large-fragment Bennett fractures. 20 Leclère and colleagues reported the long-term results of open screw fixation of 21 large-fragment Bennett fractures.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The action of the adductor pollicis and the abductor pollicis longus muscles produces displacement of the distal fragment, retraction of the first web (varus), and shortening due to dorsal dislocation. Several techniques have been described, including: locking plates, 5,6 open screw fixation, 7 and percutaneous K-wire fixation. Several techniques have been described, including: locking plates, 5,6 open screw fixation, 7 and percutaneous K-wire fixation.…”
Section: Historical Perspectivementioning
confidence: 99%
“…9 Twenty-three returned to their pre-injury work and sports. Of the 21 patients with no pre-injury degenerative changes, 10 (48%) had anatomical reduction, 7 (33%) had less than 1 mm stepoff, 3 (14%) had a < 1 mm gap, and 1 patient (5%) had a 1 mm step and gap.…”
Section: The Evidencementioning
confidence: 98%
“…There are various reported means of fixation: pins (Bennani et al, 2012;Culp and Johnson, 2010;Greeven et al, 2012;Lutz et al, 2003); screws (Leclère et al, 2012;Meyer et al, 2003;Strömberg, 1977;Tourne et al, 1988); or plates (Pavic and Malović, 2013;Uludag et al, 2013).…”
Section: Treatmentmentioning
confidence: 99%
“…Leclère et al reported their long-term results of treating 21 Bennett's fractures with a large fragment by open screw osteosyntheses. After 4 years, the overall strength of the hand was 89% of that of the contralateral side, but one patient had a secondary subluxation 9 weeks after surgery (Leclère et al, 2012). Lutz et al reported results at a mean of 7 years comparing open screw fixation to percutaneous trans-articular pinning in 32 Bennett's fractures with large fragments.…”
Section: Indicationsmentioning
confidence: 99%